Clinical study on effect of Utkleshan, Doshahara, and Samshamana basti in management of Vicharchika (Eczema) - Sumeet Saini; Muralidhar P Pujar (Wolters Kluwer Medknow Publications, 2022)
Introduction: The skin is a protective coat between the body and surrounding environment. Eczema accounts for a large proportion of skin diseases. Most of the clinical features of Vicharchika can be correlated to the clinical features of Eczema. Basti is useful in the treatment of Vata, Pitta, and Kapha doshas and even in derangement of rakta dhatu. It is a type of shodhana, in which vitiated doshas are expelled through Adhomarga, including various skin disorders because of its capacity to act over all the three doshas and plays a important role to purify the blood. As per classics, dosha utkleshana is mainly by snehana and swedana but Acharya Sushruta opines-Utkleshana of dosha's via basti. Acharya Sushruta opines basti as superior to all other therapeutic measures on account of its various action like Samshodana, Samshamana, Samgrahana, Utkleshana, etc., Hence, this study of Basti in Vicharchika may be helpful to overcome all the negative aspects of difficulty during Snehpana prior to Vaman and Virechan. Objective: To clinically evaluate the effectiveness of Basti given in the sequence of Utkleshana, Doshahara, Samshamana in kala Basti schedule in Vicharchika w. s. r. to Eczema. Methods: Thirty subjects diagnosed with Vicharchika were selected. They were administered with Niruha basti as Utkleshan, Doshahara and Samshaman basti for 2-2 days each and Anuvasana basti with Marichadi taila with 80 ml daily in Kala schedule for 9 days and assessed after 18 days of follow-up. Results: Treatment was found to be statistically significant in attaining encouraging results (P < 0.05) with respect to subjective and objective parameters during the course of basti. Conclusion: Utkleshan, Doshahara, and Samshamana basti administered in sequence is effective and useful in the management of Vicharchika (Eczema).